1984
DOI: 10.1111/j.1528-1157.1984.tb04181.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Seizures Inhibit Amygdala Kindling: Implications for Mechanisms of Action in Affective Illness

Abstract: Amygdala kindling, the progressive development of seizures following repeated electrical stimulation, has been used as a model of epileptogenesis, neural memory, and the development of behavioral alterations. In an attempt to interfere with the kindling process, electroconvulsive seizures (ECS) were administered 6 h prior to or immediately after once-daily amygdala stimulation. ECS compared with sham ECS 6 h prior to kindling profoundly inhibited the development of amygdala-kindled seizures, while ECS immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 46 publications
1
38
0
1
Order By: Relevance
“…It is unlikely that a kindling phenomenon can account for the results seen with repeated ECS since spontaneous behavioural seizures were not observed and there were no localised seizures during electrophysiological recording. There is no evidence to suggest that ECT produces kindling in human brain (Small et al 1981) and furthermore, repeated ECS inhibits the development of kindling in animals (Post et al 1984).…”
Section: Discussionmentioning
confidence: 98%
“…It is unlikely that a kindling phenomenon can account for the results seen with repeated ECS since spontaneous behavioural seizures were not observed and there were no localised seizures during electrophysiological recording. There is no evidence to suggest that ECT produces kindling in human brain (Small et al 1981) and furthermore, repeated ECS inhibits the development of kindling in animals (Post et al 1984).…”
Section: Discussionmentioning
confidence: 98%
“…Blackwood et al found that the incidence of seizures in patients following treatment with ECT was no higher than in the general population (131). In fact, several studies have shown that ECT increases seizure threshold by 50 to 100% (130,(133)(134)(135)(136). If patients are taking lithium at the time ECT is being considered, some authors have suggested that it be discontinued at least 5 days prior to ECT because of the risk of prolonged seizures, memory loss, and confusion (137).…”
Section: Choice Of Admentioning
confidence: 98%
“…ECS also increase NPY-LI in the hippocampus of FSL and normal rats (Jiménez Vasquez et al, 2000;Husum et al, 2000;Mathé et al, 1998;Stenfors et al, 1989). ECT has pronounced mood-normalizing and antipsychotic properties, but is also an anticonvulsant, as shown both in patients and in animal models of epilepsy (Nakajima et al, 2001;Post et al, 1984). Based on findings of increased hippocampal NPY release following kainic acid and ECS-induced seizures (Husum et al, 2000(Husum et al, , 1998, attenuating effects of exogenous NPY against pharmacologically induced seizures (Woldbye, 1998;Woldbye et al, 1997Woldbye et al, , 1996, increased or even fatal vulnerability of NPY knock-down and knock-out mice to seizures (DePrato Primeaux et al, 2000;Baraban et al, 1997;Erickson et al, 1996), and altered brain synthesis of NPY in seizure-prone animals (Jinde et al, 1999;Amano et al, 1996;Sadamatsu et al, 1995), NPY has been suggested to act as an endogenous anticonvulsant (Bolwig et al, 1999).…”
Section: Discussionmentioning
confidence: 99%